Regulation of precipitation‐associated vegetation dynamics on catchment water balance in a semiarid and arid mountainous watershed. Issue 7 (29th January 2016) - Tang, Guoping; Carroll, Rosemary W.H.; Lutz, Alexandra; Sun, Lin
Abstract: Quantifying the regulation of precipitation‐associated vegetation dynamics on land surface water balance poses a particular challenge in current eco‐hydrological studies because terrestrial ecological processes interact with hydrological processes, and both are subject to precipitation change. The objective of this study is to examine how precipitation change‐associated vegetation dynamics may regulate catchment water balance in a semiarid to arid mountain ecosystem. To achieve this objective, R‐RHESSys, which is short for rasterised regional hydro‐ecological simulation system, a distributed hydro‐ecological model, was applied to the Cleve Creek watershed in the eastern Nevada, USA. Simulation results from two scenarios based on altered precipitations were compared, respectively, to those from a baseline scenario based on observed precipitations. Our results suggest that R‐RHESSys can accurately simulate catchment water balance and vegetation dynamics in the study area. In addition, we found that (i) precipitation‐associated shifts in leaf canopy can help reduce flood potentials during wet years or sustain baseflow during dry years through changing evapotranspiration (ET); (ii) precipitation‐associated decrease in leaf canopy and consequent decrease in ET do not always increase streamflow and vice versa. The regulation of precipitation‐associated vegetation dynamics on streamflow is subject to initial soil water condition; (iii) vegetation‐associated shifts in plant transpiration play an important role in regulating soil water content and streamflow generation in the semiarid and arid mountain watershed; and (iv) the regulation of precipitation‐associated shift in leaf canopy on ET is more pronounced in the ridges of watershed than in valleys. In contrast, its regulation on subsurface flow generation is more remarkable in valleys than in the ridges of watershed. Copyright © 2015 John Wiley & Sons, Ltd.